Colloidal silica-bonded MgO-CaO hot gunning mixes: Characterization of physical properties, microstructure and gunning performance. Issue 17 (1st December 2019) - Cai, Manfei; Liang, Yonghe; Nie, Jianhua; Yin, Yucheng; Ju, Maoqi; Zhang, Qingxia
Abstract: Colloidal silica has been utilized as a binder agent in various areas owing to its sinterability and high permeability. However, regarding its use in MgO–CaO hot gunning mixes are lacking. In this study, phase compositions and physical properties of different colloidal silica contents on hot gunning mixes were investigated. The rebound loss rate of hot gunning mixes at 1100 °C was also evaluated via thermal simulation. In addition, the interface analysis between the gunned layer and Mag-Chrome bricks was presented, and the results were compared with those obtained using conventional phosphate-bonded mixes. The results indicate that the colloidal silica-bonded MgO–CaO hot gunning mixes achieve the appropriate mechanical strength and bulk density with 5 wt% of colloidal silica; the primary phases of mixes were forsterite and monticellite. In comparison with the conventional phosphate-bonded gunning mixes, the use of colloidal silica led to better physical properties and lower rebound loss rate under the present experimental conditions. Moreover, the gunned layers obtained were more compact and cohesive than the ones prepared using conventional phosphate-bonded mixes.